2013
DOI: 10.1108/bss-01-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and dividend policy in Indonesia

Abstract: Purpose – This study aims at examining the impact of corporate governance on dividend policy among Indonesian companies. There are two theories of the effect of corporate governance on dividend policy: substitution and outcome theory. Substitution theory argue that corporate governance have negative effect on dividend policy, while outcome theory argue that corporate governance have positive effect on dividend policy. Therefore, this study investigates the effect of corporate governance on divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 24 publications
1
40
2
2
Order By: Relevance
“…This outcome supports (Mitton, 2004;Kowalewski et al, 2008;Sawicki, 2009) and contradicts (Setiawan et al, 2013) who provided evidence showed that dividend policy is affected negatively by corporate governance. …”
Section: Logistic Regressionmentioning
confidence: 36%
See 1 more Smart Citation
“…This outcome supports (Mitton, 2004;Kowalewski et al, 2008;Sawicki, 2009) and contradicts (Setiawan et al, 2013) who provided evidence showed that dividend policy is affected negatively by corporate governance. …”
Section: Logistic Regressionmentioning
confidence: 36%
“…However, the results showed that the percentage of inside directors, the percentage of women, insiders' ownership and Directors' tenure are statistically insignificant related to dividend policy. Setiawan et al, (2013) tested the impact of corporate governance on dividend policy for a sample of 248 manufacturing firms listed on Indonesian Stock Exchange during the period [2004][2005][2006]. The study used Transparency and Disclosure Index (TDI) to measure corporate governance in Indonesia.…”
Section: Previous Researchmentioning
confidence: 99%
“…In fact, a growing number of studies have started to examine the relationship between ownership structure (e.g., families, institutional investors and the state), corporate governance (e.g., board size, board independence and CEO duality) and dividend policy in the context of emerging markets. For example, various cross-country studies, such as Mitton (2004) -19 developing countries from Latin America and Asia to Europe, Abor and Fiador (2013)four emerging markets in Sub-Saharan Africa, and Mehdi et al (2017) -362 firms from East Asia and Gulf Cooperation Council countries, and single-country studies, such as Abdelsalam et al (2008) in Egypt, Bokpin (2011) in Ghana, Setiawan and Phua (2013) in Indonesia, Benjamin and Zain (2015) in Malaysia and Al-Najjar and Kilincarslan (2016) in Turkey, have all documented the effect of ownership structure and/or corporate governance on dividend payment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This study intends to test whether firm size can strengthen the effect of profitability on dividend policy. While firm size has no effect on dividend policy [3] [21].…”
Section: Literature Reviewmentioning
confidence: 99%